A real-time profile for UML - Graf, Susanne; Ober, Ileana; Ober, Iulian (International journal on software tools for technology transfer, 2006)
This paper describes an approach for real-time modelling in UML, focusing on analysis and verification of time and scheduling-related properties. To this aim, a concrete UML profile, called the omegaprofile, is defined, dedicated to real-time modelling by identifying a set of relevant concepts for real-time modelling which can be considered as a refinement of the standard SPT profile. The profile is based on a rich concept of event representing an instant of state change, and allows the expression of duration constraints between occurrences of events. These constraints can be provided in the form of OCL-like expressions annotating the specification or by means of state machines, stereotyped as 'observers'. A framework for modelling scheduling issues is obtained by adding a notion of resource and a notion of execution time. For proving the relevance of these choices, the profile has been implemented in a validation tool and applied to case studies. It has a formal semantics and is sufficiently general and expressive to define a semantic underpinning for other real-time profiles of UML which in general define more restricted frameworks. In particular, most existing profiles handling real-time issues define a number of predefined attributes representing particular durations or constraints on them and their semantic interpretation can be expressed in the OMEGA-RT profile. [PUBLICATION ABSTRACT]